Acute Leg Ischaemia in an HIV-Infected Patient Receiving Antiretroviral Treatment. Issue 1 (January 2017) - Navarro, Jordi; Curran, Adrian; Burgos, Joaquin; Torrella, Ariadna; Ocaña, Inma; Falcó, Vicenç; Crespo, Manuel; Ribera, Esteban
An HIV-infected patient treated with tenofovir disoproxil fumarate/emtricitabine/elvitegravir/cobicistat developed severe acute ischaemia of both legs during a migraine episode. After being interrogated he admitted taking an ergotamine-containing preparation. Ergotism due to interaction between ergotics and cobicistat was diagnosed. We describe the first reported case of this interaction.